ANALISIS KESALAHAN EJAAN DAN TANDA BACA PADA MEDIA SOSIAL INSTAGRAM - Indah Septi Eka Ningrum; Ludviana Eka Purnami; Asprilia Tika Lestari (Universitas Madura, 2021)
This study aims to analyze Indonesian spelling errors in writing social media posts. The sample was taken from Instagram social media. On each account that uploads photos containing writing. This research is a descriptive research that focuses on extracting qualitative data by looking at a detailed description of the research subject. From the results of this study, in general it can be said that Indonesian language errors in social media uploads on Instagram are still common and are not in accordance with good and correct Indonesian language rules. The forms contained in writing errors include spelling, spacing, and the writing that is conveyed is not in accordance with the rules for using good and correct Indonesian. Writing errors in Instagram uploads are caused by the influence of the use of everyday language based on written and spoken language in their environment, limited knowledge of Indonesian language rules, and the tendency to imitate. In addition, they often ignore how to use good written language.